THE EFFECT OF CORPORATE GOVERNANCE ON FINANCIAL DISTRESS WITH FINANCIAL RATIO AS CONTROL VARIABLE - Valentina, Cindy; Christian, Natalis (Catholic University Musi Charitas, 2026)
Purpose : This research aims to examine the effect of corporate governance mechanisms encompassing board independence CEO tenure ownership concentration board size board diversity and audit committee size on corporate financial distress while incorporating financial ratio control mechanisms that include leverage profitability and liquidity in companies with the availability of corporate governance data and financial ratios over a defined period Design Methodology : A quantitative approach was applied The population consists of corporate entities that meet the specified criteria The sample was determined using purposive sampling resulting in selected companies as the unit of analysis Findings : Panel data regression was employed as the analytical approach using EViews as the computational tool This study addresses gaps in prior research on the relationship between corporate governance and financial distress by integrating financial ratios including leverage liquidity and profitability as control variables A comprehensive set of governance dimensions was incorporated including board independence CEO tenure ownership concentration board size board diversity and audit committee size Practical Implications : Implications are directed toward company management to strengthen governance structures and ensure that decision making and oversight functions are implemented effectively Originality Value : A comprehensive integration of corporate governance dimensions is presented including board size CEO tenure board independence ownership concentration board diversity and audit committee size which enriches the analytical framework in examining financial distress